Can an Ethnic Group Climb up from the Bottom of the Ladder? - Gil Epstein; Erez Siniver (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
Studies in the US have shown that black immigrants have remained at the bottom of the wage ladder and that other groups of immigrants have overtaken them over time. The goal of this research is to determine whether a specific group of immigrants can displace a group at the bottom of the ladder. We use Israeli data to compare two ethnic groups: Israeli Arabs and Ethiopian immigrants. Israeli Arabs were considered to be the least successful ethnic group in the Israeli labor market until they were displaced by the Ethiopian immigrants. The results of our analysis show that an ethnic group at the bottom of the wage ladder can be replaced by another.
Keywords: J15; J24; J31; 330; wage differences; immigrants